The impact of government education policies on women’s learning opportunities in Bangladesh - Samsunahar, Samsunahar; Ushama, Thameem (International Scientific Research Group (ISRG) Publishers, 2025)
This study looks into the role of government education policies in closing the gender gap in improving unbiased learning opportunities in Bangladesh. Over the last two decades, Bangladesh has pursued an advanced-prone policy to improve girls’ access to quality education, guided by commitments to gender equality, human capital development, and international frameworks such as the Education for All (EFA) goals and the Sustainable Development Goals (SDGs). Important policy initiatives, such as the Female Secondary School Scholarship Programme (FSSP), free textbook distribution, gender-sensitive curriculum reforms, school feeding programs, and investments in community-based and non-formal education, have contributed significantly to the enrollment and quality retention of girls. These initiatives have also helped to alleviate financial pressures, eradicate early marriage, and increase parental support for girls’ education. Despite these achievements, significant impediments remain. Women and girls continue to face barriers to equal participation, including socioeconomic limits, poor educational facilities, restricted access to digital technology, and safety concerns, particularly in rural and marginalized regions of the country. The COVID-19 pandemic worsened existing inequities by raising dropout rates and extending the digital learning divide. The study finds that, while government policy to improve quality education, regardless of gender disparity, has partly contributed to the formation of gender parity, the impact is uneven due to shortcomings in sound policy-making, its implementation, monitoring, and resource allocation. The study suggests that in order to close the gender gap in educational activities effectively, Bangladesh needs to fabricate and implement a more comprehensive and gender-responsive policy framework. This involves improving teaching resources, teachers training, introducing digital literacy components, increasing targeted stipends for vulnerable girls, and developing partnerships with non-governmental organizations and community stakeholders. By tackling systemic disparities and increasing policy coherence between established institutions, the government may promote sustainable progress in women’s educational advancement while also contributing to national development goals.